Luxury and Modernism : Architecture and the Object in Germany 1900-1933 - Schuldenfrei, Robin (Book collections on Project MUSE., 2018)
This beautifully illustrated book provides a new interpretation of modern architecture and design in Germany during the heyday of the Bauhaus and the Werkbund, tracing modernism's lasting allure to its many manifestations of luxury. Robin Schuldenfrei casts the work of legendary figures such as Peter Behrens, Walter Gropius, and Ludwig Mies van der Rohe in an entirely different light, revealing the complexities and contradictions inherent to modernism's promotion and consumption. Luxury and Modernism shows how luxury was present in bold, literal forms in modern designs--from lavish materials and costly technologies to deluxe buildings and household objects--and in subtler ways as well, such as social milieus and modes of living. While modernism was publicized as a fusion of technology, new materials, and rational aesthetics to improve the lives of ordinary people, it was often out of reach to the very masses it purportedly served. Schuldenfrei exposes the disconnect between modernism's utopian discourse and its luxury objects and elite architectural commissions. Despite the movement's egalitarian rhetoric, many modern designs addressed the desires of the privileged individual. Yet as Schuldenfrei demonstrates, luxury was integral not only to how modern buildings and objects were designed, manufactured, and sold, but has contributed to modernism's appeal to this day. Featuring stunning color images throughout, Luxury and Modernism provides an entirely new look at one of the most celebrated and influential eras in the history of architecture.